PENDAMPINGAN UMKM BAKSO PANGSIT GEROBAK IJO SEBAGAI UPAYA UNTUK MENINGKATKAN PENDAPATAN USAHA - Eka Wijayanti; Meilinda Dwi Cahyaningsih; Wahyu Aulia Nur Zahara; Rikah; Damayanti (LPPM ITB AAS Indonesia Surakarta, 2025)
Micro, Small and Medium Enterprises or better known as MSMEs are a type of business owned by small entrepreneurs. MSMEs are a type of business that has assets and turnover that are still relatively small. However, one of the MSMEs, namely in the food and beverage sector, is able to grow up to 6% in 2024. One of the small and medium businesses in the culinary sector that has the potential to be developed is the MSME